Hematopoietic Reprogramming Entangles with Hematopoiesis. Issue 10 (October 2020) - Wei, Chuijin; Yu, Pei; Cheng, Lin
Abstract : Hematopoiesis generally refers to hematopoietic development in fetuses and adults, as well as to hematopoietic stem cell differentiation into progeny lineages. The multiple processes that generate diverse hematopoietic cells have been considered to be unidirectional. However, many reports have recently demonstrated that these processes are not only reversible but also interconvertible via cell reprogramming. The cell reprogramming that occurs in hematopoietic cells is termed hematopoietic reprogramming. We focus on both autogenous and artificial hematopoietic reprogramming under physiological and pathological conditions that is mainly directed by the actions of transcription factors (TFs), chemical compounds, or extracellular cytokines. A comprehensive understanding of hematopoietic reprogramming will help us not only to generate desirable cells for cell therapy but also to further analyze normal and malignant hematopoiesis. Highlights: Hematopoietic reprogramming including hematopoietic cell transdifferentiation and hematopoietic cell dedifferentiation reverses and complicates the process of hematopoiesis. Hematopoietic reprogramming not only helps to update the atlas of normal hematopoietic differentiation but also contributes to the generation of desirable hematopoietic cells for cell therapy. Hematopoietic reprogramming in malignancy leads to two opposite results: it contributes to malignant hematopoietic development and releases hematopoietic malignancy. The key modulators involved in hematopoietic reprogramming include transcription factors, chemical compounds, microenvironmental factors, and potential miRNAs.